The “Collapse in Quality” Hypothesis - Levchenko, Andrei A; Lewis, Logan T; Tesar, Linda L (American Economic Review, 2011)
This paper evaluates the hypothesis that during the 2008–2009 collapse in international trade, imports of higher quality goods experienced larger reductions compared to low-quality imports, using data on US imports disaggregated by HS-10 product category and source country. We find little, if any, robust econometric evidence in support of this hypothesis.